Youth, Education and Human Rights in loss of Freedom - Débora Cardoso Campos; Fernanda Lustosa Almeida; Débora Cristina Fonseca (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
This paper aims to reflect on the educational process of young people deprived of their freedom, analyzing the conceptions of adolescence and youth and violence from teachers who teach and taught classes in the centers of Unidades de Internação da Fundação Casa (SP), from the perspective of human rights and the disease process of teachers. It is a qualitative study, which used semi-structured interviews with teachers from four centers of Unidades de Internação da Fundação Casa São Paulo state. Results showed that the educational logic is configured as similar to regular education offered in the schools integrated into the community, which shows some difficulties to provide the rights to education to young people in custody. The space of schooling seems to be stressed by explicit and implicit forms of violence experienced by / the students / as and by / the teacher. In the last case, the suffering has been configured in a disease process and or adaptation, as ways of survival at work. Once understood the rights, and confronted them with the practice, it is noticed that there is a need for a proposal of teaching and learning articulated in the context of deprivation of liberty. It makes sense to them, given guaranteeing fundamental rights to human dignity. Keywords: Youth; Schooling; Loss of Freedom.